Retraction: Yurttafl V et al. Prognostic factors for graft success in tympanoplasty with mastoidectomy. ENT Updates 2015;5:72–75 - Yurttaş, Veysel; Ural, Ahmet; Kutluhan, Ahmet; Bozdemir, Kazım (ENT Updates, 2016)
The authors of the above article discovered a significant inaccuracy in their own paper that has been published in ENT Updates 2015;5(2):72-75. They retract this publication due to duplicate publication of the same material in another issue of the same journal by mistake.